Pre-Election Campaign in the Radio and TV Programme in the Romanian Language of the Public Service of Vojvodina - Spariosu, Laura G. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The aim of this paper is to investigate the way in which the pre-election campaign is reported in the radio and TV programme in the Romanian language of the Public Service of Vojvodina. In that sense, articles on this topic were analysed in 14 radio and 14 TV central informative programmes broadcasted in March 2022. For the purposes of the research, a quantitative-qualitative method of media discourse content analysis and a comparative method were used, also a code sheet was compiled including the following categories: date, medium, duration of the radio and TV report, publication of the article (in the pre-election block or outside the block), topic, authorship, genre, audio-visual equipment, reporting occasion, location, subject, personalization of the subject, party affiliation of the subject, party name of the subject if it is a party person, object, personalization of the object, party affiliation of the object, party name of the object if it is a party person, the relation of the subject to the object, the way of advertising in the campaign, notes. The analysis of the results showed that despite the tendency of journalists to inform the audience about the activities of political parties in a timely manner, this was done through simple forms, most often news, without a critical approach. Furthermore, most of the space was given to the pre-election campaign in Belgrade and other places in Serbia, ignoring Novi Sad and Vojvodina, as well as places with Romanian population. The analysed articles most often report on current events, with an emphasis on the activities of republic officials and candidates in the presidential elections. In addition, the most represented politician is Aleksandar Vučić and the SNS political party. Therefore, we cannot consider this an example of good practice because the Public Service must be in the service of the citizens who establish and finance it, not only one party. Still, we commend the effort to report on the campaign within the electoral bloc, thus preventing abuse of office and preventing officials from being advertised from positions of power.
Keywords: pre-election campaign; public broadcaster; radio programme; TV programme; Romanian language